Progress of Near-Infrared-Based Medical Imaging and Cancer Cell Suppressors - Vicky Mudeng; Gelan Ayana; Sung-Uk Zhang; Se-woon Choe (Chemosensors, 2022)
Diffuse optical tomography, an imaging modality that utilizes near-infrared light, is a new way to assess soft tissue. It provides a non-invasive screening of soft tissue, such as the breast in females and prostate in males, to inspect the existence of cancer. This new imaging method is considered cost-effective and preferred because the implementation is simply through the application of a laser or light-emitting diode as a light source. Near-infrared technology does not only offer cancer screening modality, but also acts as a cancer treatment method, called near-infrared photoimmunotherapy. Despite plentiful studies in the area of near-infrared technology for cancer imaging and cancer cell suppression, there is no consolidated review that provides an overview of near-infrared application in cancer cell imaging and therapy. The objective of this study is to review near-infrared-based medical imaging and novel approaches to eradicate cancer cells. Additionally, we have discussed prospective instrumentation to establish cancer therapeutics apparatuses based on near-infrared technology. This review is expected to guide researchers implementing near-infrared for a medical imaging modality and cancer suppression in vitro, in vivo, and in clinical settings.